Myoclonic epilepsy, parkinsonism, schizophrenia and left-handedness as common neuropsychiatric features in 22q11.2 deletion syndrome. Issue 3 (10th September 2019) - Fanella, Martina; Frascarelli, Marianna; Lambiase, Caterina; Morano, Alessandra; Unolt, Marta; Liberati, Natascia; Fattouch, Jinane; Buzzanca, Antonino; Accinni, Tommaso; Ceccanti, Marco; Viganò, Alessandro; Biondi, Massimo; et al.
Abstract : Background: 22q11.2 deletion syndrome (22q11.2DS) is considered as the genetic model of schizophrenia. However, its polymorphic nature has led researchers to further investigate its neuropsychiatric manifestations. Methods: We enrolled 56 adults (38 men, 18 women) diagnosed with 22q11.2DS. All subjects were evaluated by a multidisciplinary team. The neuropsychiatric features were investigated by means of clinical and neurophysiological evaluation (video-EEG). Results: Thirty per cent of our patients were left-handed. Fifty-eight per cent had a low IQ, and 22 of 56 subjects had psychotic disorders (13 of 22 with schizophrenia). Eighteen patients reported at least one seizure in their lifetime, and ten were diagnosed with epilepsy; among them, seven had genetic generalised epilepsy (GGE), and five of seven showed features suggestive of juvenile myoclonic epilepsy (JME). Video-EEG recordings revealed generalised epileptiform abnormalities in 24 of 56 cases. Besides, only one patient with epilepsy had a cardiac malformation. Lastly, 31 of 56 subjects presented with parkinsonism, 16 of whom were taking neuroleptics. None of the 15 patients with parkinsonism not related to neuroleptic therapy was diagnosed with epilepsy, compared with 6 of those taking antipsychotics. Conclusions: 22q11.2DS is characterised by left-handedness and neuropsychiatric features such as cognitive impairment, schizophrenia, epilepsy and parkinsonism. GGE, mostly the JME phenotype, is the predominant epilepsy type. The significant association between 22q11.2DS and parkinsonian features confirms these patients' genetic susceptibility to parkinsonism. Despite the lack of any conclusive evidence, our study suggests a possible relationship between the analysed clinical variables: (1) an inverse correlation between low IQ/psychosis/epilepsy and major cardiac diseases; (2) a direct association between psychosis and both mental delay and epilepsy; and (3) an inverse correlation between parkinsonism and epilepsy.